2022
DOI: 10.1007/s00247-022-05327-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac volumetry using real-time MRI during free-breathing with standard cine MRI during breath-hold in children

Abstract: Background Cardiac real-time magnetic resonance imaging (RT-MRI) provides high-quality images even during free-breathing. Difficulties in post-processing impede its use in clinical routine. Objective To demonstrate the feasibility of quantitative analysis of cardiac free-breathing RT-MRI and to compare image quality and volumetry during free-breathing RT-MRI in pediatric patients to standard breath-hold cine MRI. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…The CO is one of the most important parameters to assess global cardiac function and is being calculated in several clinical conditions [ 4 , 22 , 12 ]. During exercise stress in particular, the CO provides additional use to identify severe conditions in a heart failure populations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO is one of the most important parameters to assess global cardiac function and is being calculated in several clinical conditions [ 4 , 22 , 12 ]. During exercise stress in particular, the CO provides additional use to identify severe conditions in a heart failure populations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This applies for example to patients with heart failure with preserved ejection fraction (HFpEF) [ 9 , 10 ]. Real-time CMR potentially allows reliable quantification of cardiac function during exercise stress in HFpEF but has not been validated against an invasive reference standard yet [ 11 , 12 ]. Therefore this methodological study aimed to introduce and validate a novel approach applying real-time phase-contrast imaging and directly compare it to RHC for the quantification of the CO at rest and during exercise stress in HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we would limit the complications associated with airway management, the need for monitoring equipment or ventilators, and the influence of the human factor. Several teams of radiologists have shown that apnea is not always essential to obtain images allowing a correct diagnosis in the follow-up of many congenital heart diseases in children [ 12 , 13 ]. Images can be obtained in real time while the patient remains breathing.…”
Section: Methodsmentioning
confidence: 99%
“…9 When several phases are reconstructed, the resulting images can capture the underlying motion, typically the respiratory cycle and/or the beating motion of the heart. 11,12 Triggers may also be provided by the volunteer her/himself, in voluntary fashion, as sometimes done in functional MRI (fMRI) using handheld devices with button(s)/lever(s) 13 ; in this case, the temporal changes to be resolved are associated with brain function, as opposed to physiological motion.…”
Section: How Sensor Information Gets Usedmentioning
confidence: 99%